If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2u + -3 = 3 Reorder the terms: -3 + 2u = 3 Solving -3 + 2u = 3 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2u = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 2u = 3 + 3 2u = 3 + 3 Combine like terms: 3 + 3 = 6 2u = 6 Divide each side by '2'. u = 3 Simplifying u = 3
| 6x+7=-2+7x | | 7x^2+12x+9= | | 7x-4(x+5)=16 | | x-10=-38+5x | | 42x^2-41x-8=0 | | 31+25x=-5-5 | | 7x^2+12x+9=0 | | -3x-10=70+5x | | 9x+108-8=11x | | w-1=1 | | -8(x-4)=-32 | | 5x-11=8x+25 | | 31+25x=-10 | | 100=r-30 | | 3+4x-5x=14 | | 10w+20w+200=650 | | 8x+6y=330 | | 6-(3x-5)=7x-5 | | -8+4x+6x=62 | | 2(4r+6)=8(r+2) | | 14x+12y=690 | | -3+7x-3x=-47 | | 4x-4+98=18x-4 | | 25=q-13 | | -2x-8+4x=4 | | 15=x+6x+8 | | a-4=34 | | X+28=110 | | -5p-14= | | -4/9+(-2.8)= | | -6-4x=-50 | | -5p+-14= |